Comparing the Psychological Aimlessness in Edith Wharton’s the House of Mirth and Ernest Hemmingway’s the Sun also Rises - Dewi Ulya Mailasari (Register Journal, 2010)
Aimlessness concerns about one’s existence in a society where somebody feels useless amid the society and doesn’t know the role she or he must play. This paper will examine the aimlessness experienced by the main character in the novel entitled The House of Mirth and The Sun Also Rises written by the modernism authors in 1905 and 1926. The first one realized the aimlessness in the very early age, and the life was ended through an overdose, but the later found such feeling after experiencing a war injury. Both characters were victims of the situation but they seemed to have reached a more realistic appreciation of their situation.  Keywords;  Aimlessness; Psychological Consequences;  Main Characters